ANALISIS KEBIJAKAN DAN RUMUSAN PENGELOLAAN DAS BERBASIS MASYARAKAT DI SUB GENDOL PASCA ERUPSI GUNUNGAPI MERAPI 2010 (KASUS: DESA KEPUHARJO KABUPATEN SLEMAN) - , IKA AFIANITA SUHERNINGTYAS ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Mount Merapi eruption in 2010 caused environmental damage watersheds around the slopes of Mount Merapi. Kepuharjo village located on the banks of the River Gendol a rural area that is affected the most widely 99,02% of the entire area of the Village Kepuharjo. Watershed management implemented after the eruption important for physical rehabilitation and socio-economic conditions of the community. The purpose of this study was to determine the impact of environmental changes after the eruption, determine and evaluate watershed management policies after the eruption, and formulate watershed management based Participatory Mapping in Sub-watershed Gendol Kepuharjo village. The method used in this study is a qualitative method to conduct semistructured interviews, field surveys, FGD (Focus Group Discussion) and Participatory Mapping. Semi-structured interviews conducted with the purpose of research related interviews with key persons, while the FGD and Participatory Mapping done by village residents Kepuharjo. Data processing is done with ArcGIS software and qualitative analysis of the results of research in the field. The results showed that the impact of morphological changes Gendol Subwatershed is a long river before the eruption of 13,4 km to 17,1 km changed after the eruption. Regions affected by the eruption in Cangkringan include residential land (641,741 Ha), forest land (415,567 Ha), farm land (2020,784 Ha), and paddy fields (1221,383 Ha). Environmental management policy after the eruption is divided into five main sectors, namely settlements and housing, infrastructure, social, economic productivity, and cross-sector. Policies that have been implemented by 65% already implemented, 30% are still in the process, and 5% have not been implemented. Spatially and visually, the results of policy formulation using Participatory Mapping shows people's desire in the greening program in disaster-prone areas and flood plains. In addition, people also want the management of tourism development to improve the community's economy.